ITACA: A new validated international erythropoietic stimulating agent‐response score that further refines the predictive power of previous scoring systems. Issue 10 (29th July 2017) - Buckstein, Rena; Balleari, Enrico; Wells, Richard; Santini, Valeria; Sanna, Alessandro; Salvetti, Chiara; Crisà, Elena; Allione, Bernardino; Danise, Paolo; Finelli, Carlo; Clavio, Marino; Poloni, Antonella; et al.
Abstract: Background: In 'real‐life', the Nordic score guides Erythropoietic stimulating agent (ESA) use in lower‐risk myelodysplastic syndrome (MDS) with predicted response rates of 25% or 74%. As new treatments emerge, a more discriminating score is needed. Objectives: To validate existing ESA predictive scores and develop a new score that identifies non‐responders. Methods: ESA‐treated patients were identified in 3 MDS registries in Italy and Canada (FISM 555, GROM 233, and MDS‐CAN 208). Clinical and disease‐related variables were captured. Nordic, MDS‐CAN, and IPSS‐R‐based ESA scores were calculated and documented ESA responses compared. Results: 996 ESA‐treated patients were identified. Overall response rate (ORR) was 59%. The database was randomly divided into balanced derivation (n = 463) and validation (n = 462) cohorts. By multivariate analysis, transfusion independence, erythropoietin (EPO) level <100 IU/L, and IPSS low‐risk were independently predictive of response. Assigning a score of 1 to each resulted in a scoring system of 0‐3 with response rates of 23%, 43%, 67%, and 85%. ORR was concordant in the validation cohort. The 'ITACA' score had the highest discriminating power of response. Conclusion: ITACA is an internally‐validated predictive SS of ESA response in real‐life 'good risk' MDS patients derived from a large international dataset that surpasses others. The incorporation of biologic markers to better identify non‐responders is still needed.